UEG Week 2013 highlights: putting endoscopy into perspective - Papanikolaou, Ioannis S.; Siersema, Peter D. (Endoscopy, 2013)
The 21st United European Gastroenterology (UEG) Week was held in Berlin in October 2013 and presented the opportunity for those interested in gastrointestinal endoscopy to learn of recent developments and research trends from all over the world. This report highlights oral presentations of the most important and exciting topics in gastrointestinal endoscopy and reviews them in the context of current knowledge.